2022
DOI: 10.3389/fchem.2022.925881
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Food Additives Using a Fluorescence Indicator Based on 6– p–Toluidinylnaphthalence-2-sulfonate and Cationic Pillar[6]arene

Abstract: The current study investigated host-guest complexation in 6-p-toluidinylnaphthalene-2-sulfonate (TNS), a fluorescence probe used to investigate hydrophobic regions that contain the water-soluble cationic pillar[6]arene (CP6). After complexation with CP6, the fluorescence intensity of TNS was significantly increased. The decreases in the fluorescence intensity of the TNS•CP6 complex when phenolic food-additives are added have been used in indicator displacement assays to detect food additives in the water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Recently, the authors of this mini-review reported a novel fluorescence activation switch based on the host-guest complexation between a fluorescent indicator probe 6- p -toluidinylnaphthalene-2-sulfonate ( TNS ) and water-soluble pillar[6]arene dodecyl-ammonium chloride ( P6DAC ). The complexation remarkably increased the fluorescence intensity, and adding food additives (p-coumaric acid, trans-ferulic acid and gallic acid) to the TNS ⊂ P6DAC complex results in the displacement of TNS and thus causes a turn-off fluorescence response, which was employed for the F-IDA detection of phenolic food additives ( Duan et al, 2022 ).…”
Section: Pillar[ N ]Arenes-based Fluorescent Indic...mentioning
confidence: 99%
“…Recently, the authors of this mini-review reported a novel fluorescence activation switch based on the host-guest complexation between a fluorescent indicator probe 6- p -toluidinylnaphthalene-2-sulfonate ( TNS ) and water-soluble pillar[6]arene dodecyl-ammonium chloride ( P6DAC ). The complexation remarkably increased the fluorescence intensity, and adding food additives (p-coumaric acid, trans-ferulic acid and gallic acid) to the TNS ⊂ P6DAC complex results in the displacement of TNS and thus causes a turn-off fluorescence response, which was employed for the F-IDA detection of phenolic food additives ( Duan et al, 2022 ).…”
Section: Pillar[ N ]Arenes-based Fluorescent Indic...mentioning
confidence: 99%
“…However, the excessive use and accumulation of food additives in the environment is gradually increasing and is responsible for significant environmental concern. In this context, Duan et al prepared a novel FID assay based on a cationic PA[6] ( CP6 ) for the detection of some vital phenolic food additives, such as p -gallic acid ( GA ), trans-ferulic acid ( FA ) and coumaric acid ( CA ) ( Duan et al, 2022a ). The 6- p -toluidinylnaphthalene-2-sulfonate ( TNS ) was used as the fluorescent indicator in this FID system due to its enhanced emission in non-polar environments.…”
mentioning
confidence: 99%